PREDICT THE NUMBER OF NEW STUDENTS IN THE ACCEPTANCE STMIK JAKARTA (STI&K) BY COMPARING THE INDUCTIVE STATISTICAL USING SEMI AVERAGE METHOD AND METHOD LEAST SQUARES - Johan Sharif; Aqwam Rosadi Kardian. Skom. MM (Jurnal Sistem Informasi, 2002)
Based on the presumption that the new reception at STMIK Jakarta experienced adecline, then the author tries to analyze and admissions data megkaji STMIK Jakarta,to prove the allegation. The author also tries to predict the number of admissions ofnew students next year, as consideration for the conductor STMIK Jakarta (STI & K)to take steps that in the future. The writing method used by the writer is literaturestudy method and interview method. The conclusion is indeed true number ofadmissions STMIK Jakarta (STI & K) has decreased.